Heart Uptake of [18F]Fluoro-4-Thia-Oleate in a Non-Alcoholic Fatty Liver Disease Mouse Model - Junfeng Li; Weidong Hu; Jiangling Peng; Patty Wong; Fouad Kandeel; Tove Olafsen; John E. Shively (MDPI AG, 2022)
The world-wide high incidence of non-alcoholic fatty liver disease (NAFLD) is of concern for its progression to insulin resistance, steatohepatitis and cardiovascular disease (CVD). The increased uptake of fatty acids in critical organs plays a major role in NAFLD progression. Male Ceacam1−/− mice that develop NAFLD, insulin resistance and CVD on normal chow are a potential model for studying the dysregulation of fatty acid uptake. [18F]fluoro-4-thia-oleate ([18F]FTO) was chosen as a fatty acid reporter because of its higher uptake and retention in the heart in an animal model of CVD. Male wild-type (WT) or Ceacam1−/− mice fasted 4-6 h were administered [18F]FTO i.v., and dynamic PET scans were conducted in an MR/PET small animal imaging system along with terminal tissue biodistributions. Quantitative heart image analysis revealed significantly higher uptake at 35 min in Ceacam1−/− (6.0 ± 1.0% ID/cc) vs. WT (3.9 ± 0.6% ID/cc) mice (p = 0.006). Ex vivo heart uptake/retention (% ID/organ) was 2.82 ± 0.45 for Ceacam1−/− mice vs. 1.66 ± 0.45 for WT mice (p < 0.01). Higher kidney and pancreas uptake/retention in Ceacam1−/− was also evident, and the excretion of [18F]FTO into the duodenum was observed for both WT and Ceacam1−/− mice starting at 10 min. This study suggests that the administration of [18F]FTO as a marker of fatty acid uptake and retention may be an important tool in analyzing the effect of NAFLD on lipid dysregulation in the heart.